HOW TO NURTURE SCHOOL CHILDREN’S CREATIVITY IN THE CLASSROOM (Konferensiyalar | Conferences, 2024)
A study examines how second-grade instructors assess creativity in order to gain a better understanding of how creativity can be developed in general education classrooms, as well as identify barriers to nurturing creativity.